THE INFLUENCE OF WORK ETHIC AND ORGANIZATIONAL CULTURE ON EMPLOYEE INTEGRITY WITH COMPENSATION AS AN INTERVENING VARIABLE AT THE REGIONAL FINANCE AND ASSET AGENCY OF NORTH SUMATRA PROVINCE - Bambang Aditya Irsandi; Elfitra Desy Surya; Mesra B (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the influence of work ethic and organizational culture on employee integrity with compensation as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. The research approach used is quantitative with a survey method by distributing questionnaires to employees as respondents. The sample was determined using a purposive sampling technique to ensure that the data obtained is relevant to the research objectives with a total of 80 respondents. The collected data were analyzed using path analysis techniques to determine the direct and indirect effects between variables. The results of the study indicate that work ethic and organizational culture, both directly and indirectly, have a positive and significant effect on employee integrity and through compensation. In addition, compensation has a positive and significant effect on employee integrity. Work ethic also has a positive and significant effect on employee integrity, but organizational culture has a positive but insignificant effect on employee integrity. Thus, compensation is proven to mediate the influence of work ethic and organizational culture on employee integrity. The findings of this study are expected to be input for management in improving employee integrity through strengthening work ethic, implementing a positive organizational culture, and providing fair and appropriate compensation.